Xylem refilling – a question of sugar transporters and pH?. (25th July 2016) - Hacke, Uwe G.; Laur, Joan
Abstract : This article comments on: Accumulation of sugars in the xylem apoplast observed under water stress conditions is controlled by xylem pH Abstract : This article comments on: Accumulation of sugars in the xylem apoplast observed under water stress conditions is controlled by xylem pH